2023
DOI: 10.3390/nu15010228
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Dyslipidemia through Targeted Therapy of Gut Microbiota

Abstract: Dyslipidemia is a multifaceted condition with various genetic and environmental factors contributing to its pathogenesis. Further, this condition represents an important risk factor for its related sequalae including cardiovascular diseases (CVD) such as coronary artery disease (CAD) and stroke. Emerging evidence has shown that gut microbiota and their metabolites can worsen or protect against the development of dyslipidemia. Although there are currently numerous treatment modalities available including lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 203 publications
0
10
0
Order By: Relevance
“…13 All these parameters were modified upon maternal treatment with cholestyramine in our study. Furthermore, it is described that cholestyramine treatment could enhance both antiinflammatory status and gut microbiota 29 in dams, and in turn influence inflammation and microbial composition and metabolites in offspring. 30,31 Then, we further examined the effect of maternal cholestyramine treatment on some risk factors F I G U R E 3 acid in gallbladder and plasma of offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 All these parameters were modified upon maternal treatment with cholestyramine in our study. Furthermore, it is described that cholestyramine treatment could enhance both antiinflammatory status and gut microbiota 29 in dams, and in turn influence inflammation and microbial composition and metabolites in offspring. 30,31 Then, we further examined the effect of maternal cholestyramine treatment on some risk factors F I G U R E 3 acid in gallbladder and plasma of offspring.…”
Section: Discussionmentioning
confidence: 99%
“…All these parameters were modified upon maternal treatment with cholestyramine in our study. Furthermore, it is described that cholestyramine treatment could enhance both anti‐inflammatory status and gut microbiota 29 in dams, and in turn influence inflammation and microbial composition and metabolites in offspring 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Diet directly affects the composition of the gut microbial communities and the production of metabolites. Cellular stress caused by unhealthy diets, such as a high intake of high-fat foods, animal byproducts, and processed foods, may influence abnormal lipid metabolism and cerebral small vessel disease, which can trigger the neuroinflammatory process and, as a result, activate a neurodegenerative cascade (Nassir et al, 2021;Flaig et al, 2023). Foods high in choline and L-carnitine, such as red meat, can be metabolized by intestinal microbiota to produce trimethylamine N-oxide (TMAO), which has been shown in experimental and clinical studies to promote the occurrence of atherosclerosis and stroke (Koeth et al, 2013;Zhu et al, 2021).…”
Section: Dietary Interventions In Ismentioning
confidence: 99%
“…Recent research has identified the gut microbiota as a potential therapeutic target [ 10 ]. The gut microbiota plays a crucial role in metabolism regulation, immune modulation, and maintaining gut mucosal integrity [ 11 ]. It has been implicated in the onset and progression of AD, with abnormal gut bacterial colonization disrupting the Th1/Th2 balance and exacerbating AD[ [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%